QUALITY OF SERVICE FOR BUILDING PERMITS AT THE OFFICE OF INVESTMENT AND INTEGRATED SERVICES ONE PINTU (DPMPTSP) PALOPO CITY - Hamid, Ardian Sukmawan; Aslinda, Andi; Sakawati, Herlina (Universitas Negeri Makassar, 2025)
This research aims to find out the quality of public services in granting building construction permits in Palopo City and what are the supporting and inhibiting factors in granting building construction permits in Palopo City. To achieve this goal, researchers used data collection techniques through observation, interviews and documentation. The data obtained from the research results were processed using qualitative analysis to find out what the quality of public services is in granting building construction permits in Palopo City and what are the supporting and inhibiting factors in granting building construction permits in Palopo City. The research results show that the quality of building permit services at the Palopo City Investment and One-Stop Integrated Services Service (DPMPTSP). based on the service quality indicators of Zeithmal-Parasuraman-et al in Mulyawan (2016: 64), namely Direct Evidence, Reliability, Responsiveness, Attitude are quite good but still need to be optimized for each indicator. This is proven based on the results of interviews that have been conducted. Suggestions: 1) in terms of additional computer facilities to improve online services so that it can facilitate public access in applying for permits online. 2) staff have responded well in providing services to the public who use permit requests so a consistent attitude is needed in this dimension so that Service quality can be well maintained. 3) Timeliness is a problematic factor in this dimension, so a level of discipline is needed, especially in time management.